Nano-Biochar: A promising tool for sustainable agriculture under climate change era - Nallagatla Vinod Kumar; K.N. Pallavi; Priyadarshani Rajput; B. Bhargavi; Mandapelli Sharath Chandra; Pebbeti Chandana; Rayapati Karthik; L. Peace Raising; Naveen Kumar; Rajan Bhatt; Tatiana Minkina; Vishnu D Rajput (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Nano-biochar, a highly porous and innovative material derived from biomass, presents significant opportunities for sustainable agriculture and environmental remediation. Its unique sponge-like structure enables exceptional carbon capture and sequestration, contributing to long-term improvements in soil fertility and acting as a vital tool in climate change mitigation. This review explores the properties and production methods of nano-biochar, highlighting its enhanced nutrient retention, controlled release capabilities, and superior water-holding capacity compared to traditional biochar. These characteristics not only enhance plant growth and agricultural productivity but also promote a healthier soil ecosystem by stimulating microbial activity. Furthermore, nano-biochar's ability to adsorb heavy metals and organic pollutants offers promising applications in soil and water remediation, thus preventing environmental contamination. Despite its numerous advantages, the review identifies critical knowledge gaps regarding the long-term ecological impacts of nano-biochar and the best practices for its production and application. The paper calls for further research to address these challenges and optimize the use of nano-biochar, ensuring its responsible development within agricultural systems. By integrating insights from current literature, this review contributes to a comprehensive understanding of nano-biochar's potential and outlines future research directions to enhance its effectiveness in promoting sustainable agricultural practices.